2018
DOI: 10.2139/ssrn.3188435
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrically Positioned Flagellar Control Units Regulate Human Sperm Rotation

Abstract: Highlights d Sperm proton channels form asymmetrically positioned bilateral flagellar lines d The flagellar ion channels of human sperm are organized in nanodomains d The nanodomains are comprised of Hv1, CatSper, and ABHD2, ensuring concerted regulation d Asymmetrical organization of Hv1 is responsible for sperm rotation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…5E), in contrast with the circular arcs in Chlamydomonas mutants (29). Our observations are consistent with reports showing a hierarchy of distinct asymmetries in flagellar systems, from asymmetric distribution and activity of molecular motors (25,31,32) to asymmetric bending in hamster spermatozoa (37), asymmetric static modes in Chlamydomonas (23,27), atypical centriole (33), and an ever growing number of asymmetric regulatory complexes (10,27,29,34,35) in addition to other unknown biases from less well-studied motor proteins (36). While the exact molecular mechanism underlying the observed asymmetric static shape is still unknown (23,27), our results show that, together with murine spermatozoa (37) and Chlamydomonas flagellum (23), the human sperm flagellum is part of the asymmetric beating-flagellated microorganisms that exhibit an intrinsically asymmetric static mode, reflecting potential universal asymmetries across species.…”
Section: Molecular and Structural Origin Of Beating Asymmetry And Anisupporting
confidence: 91%
See 2 more Smart Citations
“…5E), in contrast with the circular arcs in Chlamydomonas mutants (29). Our observations are consistent with reports showing a hierarchy of distinct asymmetries in flagellar systems, from asymmetric distribution and activity of molecular motors (25,31,32) to asymmetric bending in hamster spermatozoa (37), asymmetric static modes in Chlamydomonas (23,27), atypical centriole (33), and an ever growing number of asymmetric regulatory complexes (10,27,29,34,35) in addition to other unknown biases from less well-studied motor proteins (36). While the exact molecular mechanism underlying the observed asymmetric static shape is still unknown (23,27), our results show that, together with murine spermatozoa (37) and Chlamydomonas flagellum (23), the human sperm flagellum is part of the asymmetric beating-flagellated microorganisms that exhibit an intrinsically asymmetric static mode, reflecting potential universal asymmetries across species.…”
Section: Molecular and Structural Origin Of Beating Asymmetry And Anisupporting
confidence: 91%
“…The postulation of symmetric beating is, however, in contrast with the abundance of observations showing structural asymmetries within the flagellar scaffold (2,10,20,23,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Asymmetric waves have been reported in murine spermatozoa (37,38), while a one-sided stroke is commonly observed in Chlamydomonas (23,(27)(28)(29).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this regard, it was recently reported the asymmetrically distribution of Hv1 channel in the human sperm flagellum, which is responsible, at least in part, for the increase in pHi (Lishko et al, 2010). This specific localization of Hv1 could produce local alkalization when positioned in close proximity to a subset of CatSper channels resulting in asymmetric local Ca 2+ changes that may be required for the complex movement of the sperm flagellum (Miller et al, 2018). In mouse, the alkalinization of the cytoplasm during capacitation occurs as a result of Na + -H + exchangers (NHE) (Chávez et al, 2014;Wang et al, 2003;Wang et al, 2007) since there is no clear evidence showing a significant role of Hv1 channels.…”
Section: Discussionmentioning
confidence: 98%
“…This segregated localization of proteins in the tail may provide the structural basis for the selective activation of CatSper and the normal development of hyperactivated motility. For example, recent superresolution microscopy experiments in human sperm revealed that Hv1, the voltagegated proton channel involved in cytoplasmic alkalinization, is distributed asymmetrically within bilateral longitudinal lines and that inhibition of this channel leads to a decrease in sperm rotation along the long axis (Miller et al, 2018). In addition, other signaling molecules such as Caveolin-1, phosphorylated Ca 2+ /calmodulindependent protein kinase II (P-CaMKII), calcineurin (PPP3C aka PP2B) and EFCAB9 colocalize with CatSper displaying a similar spatial distribution along the principal piece in mouse sperm (Chung et al, 2014;Hwang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%